2012
DOI: 10.1097/sla.0b013e318251ee09
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Distal Pancreatectomy Is Associated With Significantly Less Overall Morbidity Compared to the Open Technique

Abstract: LDP has lower blood loss and reduced length of hospital stay. There was a lower risk of overall postoperative complications and wound infection, without a substantial increase in the operative time. Although a thorough evaluation of oncological outcomes was not possible, the rate of margin positivity was comparable to the open technique. The improved complication profile of LDP, taken together with the lack of compromise of margin status, suggests that this technique is a reasonable approach in selected cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
317
3
13

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 478 publications
(348 citation statements)
references
References 54 publications
15
317
3
13
Order By: Relevance
“…It is noteworthy that there is a recent trend toward an increased size of the excised lesions (4.0 ± 2.8 cm vs. 3.3 ± 1.5 cm) noted in the literature. [20] Consistent with previous studies, [14,15] our operative time for LDP was longer than for ODP (median 195.5 vs. 112.5 min). Shin et al [22] reported a median operative time of 195 min for LDP, whereas Braga et al [28] reported a median duration of surgery of 239 min for LDP, significantly higher than that for ODP (213 min), but their series included a high rate (30%) of adenocarcinomas.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is noteworthy that there is a recent trend toward an increased size of the excised lesions (4.0 ± 2.8 cm vs. 3.3 ± 1.5 cm) noted in the literature. [20] Consistent with previous studies, [14,15] our operative time for LDP was longer than for ODP (median 195.5 vs. 112.5 min). Shin et al [22] reported a median operative time of 195 min for LDP, whereas Braga et al [28] reported a median duration of surgery of 239 min for LDP, significantly higher than that for ODP (213 min), but their series included a high rate (30%) of adenocarcinomas.…”
Section: Discussionsupporting
confidence: 80%
“…[5] More recently, several studies and meta-analyses have shown that LDP is a safe procedure, with improved outcomes and reduced hospital stays. [13][14][15][16] Cao et al [12] in their population-based retrospective cohort study reported a reduction of 1.22 days in LoS associated with minimally invasive surgery, with no differences in the perioperative mortality and total hospital costs. Furthermore, lower rates of infectious complications (30.1% vs. 39%) and bleeding complications (13.1% vs. 20.6%) were reported in LDP vs. ODP.…”
Section: Discussionmentioning
confidence: 99%
“…LDP has rapidly expanded its application over the last decade and, although randomized studies are lacking, recent meta-analyses [2][3][4][5] have suggested that LDP was safe and effective as open distal pancreatectomy. Nevertheless, Rosales-Velderrain et al [6] have reported that, in the United States, only a low percentage (15%-27%) of patients with body/tail pancreatic tumors were subjected to LDP.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Recent systematic reviews and meta-analyses [2][3][4][5] have demonstrated the safety and feasibility of LDP for benign and malignant pancreatic lesions and have reported postoperative outcome advantages with respect to an open approach.…”
Section: Introductionmentioning
confidence: 99%
“…These operations can be performed by laparoscopic procedures that add all benefits of minimally invasive procedures to the patient like less blood loss and shorter hospitalization. Even overall complication rate is less in laparoscopic distal pancreatectomy compared to open procedures (33.9 vs. 44.2 %) [1]. Therefore, this type of surgery is widely accepted and frequently performed for indications regarding the distal area of the pancreas.…”
Section: Introductionmentioning
confidence: 99%